Multifunctional Photoactive Nanomaterials for Photodynamic Therapy against Tumor: Recent Advancements and Perspectives - Rupesh Jain; Shambo Mohanty; Ila Sarode; Swati Biswas; Gautam Singhvi; Sunil Kumar Dubey (MDPI AG, 2022)
Numerous treatments are available for cancer, including chemotherapy, immunotherapy, radiation therapy, hormone therapy, biomarker testing, surgery, photodynamic therapy, etc. Photodynamic therapy (PDT) is an effective, non-invasive, novel, and clinically approved strategy to treat cancer. In PDT, three main agents are utilized, i.e., photosensitizer (PS) drug, oxygen, and light. At first, the photosensitizer is injected into blood circulation or applied topically, where it quickly becomes absorbed or accumulated at the tumor site passively or actively. Afterward, the tumor is irradiated with light which leads to the activation of the photosensitizing molecule. PS produces the reactive oxygen species (ROS), resulting in the death of the tumor cell. However, the effectiveness of PDT for tumor destruction is mainly dependent on the cellular uptake and water solubility of photosensitizer molecules. Therefore, the delivery of photosensitizer molecules to the tumor cell is essential in PDT against cancer. The non-specific distribution of photosensitizer results in unwanted side effects and unsuccessful therapeutic outcomes. Therefore, to improve PDT clinical outcomes, the current research is mostly focused on developing actively targeted photosensitizer molecules, which provide a high cellular uptake and high absorption capacity to the tumor site by overcoming the problem associated with conventional PDT. Therefore, this review aims to provide current knowledge on various types of actively and passively targeted organic and inorganic nanocarriers for different cancers.